Medicina baseada em evidências: Uma interpretaç\~ao crítica e implicaç\~oes para as políticas públicas - Maurício Mota Saboya Pinheiro; Roberto Passos Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This text aims at exploring the literature about Evidence-Based Medicine (EBM), concerning its theoretical and empirical development. One intends to identify its main issues in the domains of epistemology and ethics, as well as extracting some lessons from these issues to the Evidence-Based Policymaking (EBP). What are the main challenges of EBM concerning the well-being of individual patients? To answer this question, we need a comprehensive analysis, but one that focus on the "EBM philosophy of science" - its epistemological foundations, the structures of its scientific explanations, the role of values in scientific knowledge, as well as the ethical consequences of clinical decisions.
Keywords: I18; 330; evidence-based medicine; evidence-based policymaking; epistemology; ethics